PENGARUH ZAKAT DAN IMPLEMENTASI SOSIAL PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN SYARIAH (Studi Kasus Pada Perbankan Syariah Indonesia Periode Tahun 2017-2020) - Hairul Hairul; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine the effect of zakat and corporate social implementation on corporate financial performance in Islamic banking in Indonesia for the period 2017 – 2020 simultaneously and partially. The population and sample in this study are 14 Islamic Commercial Banks. In this study using method multiple linear regression analysis. The results show that: (1) Zakat as a corporate social implementation has a simultaneous effect on the financial performance of Islamic banking companies in Islamic banks in Indonesia for the period 2017 – 2020; (2) Zakat has an effect on the financial performance of Islamic banking companies in Islamic banks in Indonesia for the period 2017 – 2020; (3) The implementation of corporate social responsibility has no effect on the financial performance of Islamic banking companies in Indonesia for the period 2017 – 2020. Keywords: Zakat, Corporate Social Implementation, Financial Performance